2007
DOI: 10.1061/(asce)1527-6988(2007)8:4(97)
|View full text |Cite
|
Sign up to set email alerts
|

Benefit-Cost Analysis of FEMA Hazard Mitigation Grants

Abstract: Mitigation ameliorates the impact of natural hazards on communities by reducing loss of life and injury, property and environmental damage, and social and economic disruption. The potential to reduce these losses brings many benefits, but every mitigation activity has a cost that must be considered in our world of limited resources. In principle benefit-cost analysis (BCA) can be used to assess a mitigation activity's expected net benefits (discounted future benefits less discounted costs), but in practice thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
136
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(141 citation statements)
references
References 10 publications
0
136
0
1
Order By: Relevance
“…46 Reductions in ozone precursors reduce illness and death related to air pollution, as well as associated costs. Another study-of a sample of grants to mitigate hazard losses 47 -has demonstrated that the benefits of reducing climate-related hazards are considerable and outweigh the costs by a factor of 5.0:1 for flooding and 3.9:1 for wind.…”
Section: Discussionmentioning
confidence: 99%
“…46 Reductions in ozone precursors reduce illness and death related to air pollution, as well as associated costs. Another study-of a sample of grants to mitigate hazard losses 47 -has demonstrated that the benefits of reducing climate-related hazards are considerable and outweigh the costs by a factor of 5.0:1 for flooding and 3.9:1 for wind.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the new HAZUS model was released by the Federal Emergency Management Agency (FEMA) in 2004. Originally, only capable of modeling earthquake loss, the latest version of HAZUS-MH (MH stands for multi-hazard) also includes tools for flood and wind loss estimation, runs on a ArcGIS platform and provides default data so that standardized risk assessment can be performed [Beckmann and Simpson, 2006;Rose et al, 2007].…”
Section: Flood Loss Estimationmentioning
confidence: 99%
“…To reduce future flood losses in a sustainable manner, flood risk management has to be built upon a sound analysis and assessment of the flood hazard, potential losses and the effectiveness of different mitigation measures. In fact, risk analyses and risk-oriented design, in which the cost-effectiveness of flood defense schemes is evaluated, are gaining more and more attention in water and planning agencies [e.g., ResendizCarrillo and Lave, 1990;USACE, 1996;Olsen et al, 1998;Al-Futaisi and Stedinger, 1999;Ganoulis, 2003;Rose et al, 2007]. Moreover, risk analyses quantify the risks and thus enable communities and people to prepare for disasters [e.g., Takeuchi, 2001;.…”
Section: Introductionmentioning
confidence: 99%
“…Generating such research requires a commitment to applying the lessons learned to measure and design high-performing public health systems. One future research endeavor could be to conduct a cost-benefit savings analysis in public health response costs, or in mortality or morbidity averted, similar to the work of Rose et al 22 Taken together, the research described in this supplement has the potential to transform the public health preparedness field in significant ways and to inform PHPR decision making while highlighting the collaborative efforts of academic researchers, public health officials and their partners, and CDC. The PERRC research presented in this supplement and elsewhere 18 has demonstrated that using PHSSR methods can identify effective interventions and practices that improve PHPR systems and services.…”
Section: Continuous Improvement Designed Within the Interventionmentioning
confidence: 98%